2020
DOI: 10.1002/imhj.21880
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of early relational disturbance in high‐risk populations: Borderline personality disorder features, maternal mental state, and observed interaction

Abstract: Despite the longstanding theoretical association in the attachment literature between maternal trauma history and disturbances in the mother-infant interaction, few studies have investigated mechanisms of transmission of traumatogenic relational patterns in high-risk mother-infant dyads. This study investigated interrelationships among maternal trauma history, distorted maternal representations (DMRs, i.e. disturbed thoughts and feelings about the infant and selfas-parent), maternal mentalisation (i.e. capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…The greatest deficits in interaction quality are characterised by disorganisation, including confusion, inconsistency, or frightening behaviours and affect (Van Ijzendoorn et al, 1999). Researchers have shown maternal disorders and certain personality traits (Hazell Raine et al, 2020; Lorenzini and Fonagy, 2013) particularly those characterised by greater emotional dysregulation, such as borderline personality disorder, to have adverse associations with mother–infant relationship quality, including EA (Kim et al, 2012; Kluczniok et al, 2018; Newman-Morris et al, 2020). Accordingly, the inconsistency in mood that is characteristic of BD could be a potential mechanism underlying the lower EA associated with BD compared to MDD.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest deficits in interaction quality are characterised by disorganisation, including confusion, inconsistency, or frightening behaviours and affect (Van Ijzendoorn et al, 1999). Researchers have shown maternal disorders and certain personality traits (Hazell Raine et al, 2020; Lorenzini and Fonagy, 2013) particularly those characterised by greater emotional dysregulation, such as borderline personality disorder, to have adverse associations with mother–infant relationship quality, including EA (Kim et al, 2012; Kluczniok et al, 2018; Newman-Morris et al, 2020). Accordingly, the inconsistency in mood that is characteristic of BD could be a potential mechanism underlying the lower EA associated with BD compared to MDD.…”
Section: Discussionmentioning
confidence: 99%
“…The overall PRF was not significantly correlated with maternal structuring and non-intrusiveness in two studies with psychosocial high-risk mothers and mothers without risk status ( Perry et al, 2015 ; Newman-Morris et al, 2020 ). In one of the two studies, the overall PRF was significantly correlated with maternal non-hostility , showing a medium-sized effect ( Newman-Morris et al, 2020 ).…”
Section: Resultsmentioning
confidence: 80%
“…For both positive and negative parenting constructs, the effect sizes of the association with PRF and its sub-dimensions are mainly small to nearly medium. Only one study found a large-sized effect ( Hasselbeck, 2015 ), while four studies found medium- to nearly large-sized effects, all using bivariate statistical methods ( Grienenberger et al, 2005 ; Ensink et al, 2019 ; Newman-Morris et al, 2020 ; Suardi et al, 2020 ). Six studies reported associations based on both bivariate and multivariate statistical methods, of which over half of them revealed a considerable alteration of the bivariate effect ( Huth-Bocks et al, 2014 ; Hasselbeck, 2015 ; Buttitta et al, 2019 ; Newman-Morris et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An under-researched possibility is that above and beyond those manifest features of expecting mothers and pregnancies, level of personality functioning might be a key factor in identifying vulnerable pregnant women. Indeed, pregnant women with borderline features have already been identified as a high-risk group likely to experience emotional regulation and mentalization difficulties with aspects of parenting, resulting in a myriad of neurodevelopmental, psychological, relational, and behavioral consequences in the offspring (e.g., Blankley et al, 2015;Newman-Morris et al, 2020). Studying the level of personality functioning may also provide indications for gradated levels of monitoring and care, based on the level of personality dysfunction.…”
Section: Personality Pathology In Pregnant Womenmentioning
confidence: 99%